Exploring patient perception of success and benefit in self-management of breast cancer-related arm lymphoedema. (February 2016) - Jeffs, Eunice; Ream, Emma; Shewbridge, Amanda; Cowan-Dickie, Siobhan; Crawshaw, Diana; Huit, Martine; Wiseman, Theresa
Abstract: Purpose: The aim of this study was to identify factors influencing patient perception of success and benefit with self-management of breast cancer-related lymphoedema (BCRL) and explore how patients decide whether their swollen limb has improved or deteriorated. Methods: This qualitative study used a Grounded Theory approach. Twenty-one women in the BCRL self-management phase participated in one in-depth interview exploring their experience and perspective on self-managing their BCRL. Findings: Seven enablers and blocks to self-management were identified: routine, recognising benefit of self-management and consequences of non-treatment, owning treatment, knowledge and understanding, problem-solving, time required for treatment and aesthetics of hosiery. Women determined treatment outcome by monitoring size, appearance, texture and internal sensations within the affected arm. Conclusions: Women who participated in this study showed varying degrees of acceptance and adjustment to life with lymphoedema. This appears to directly impact their ability to self-manage lymphoedema. Lymphoedema practitioners and oncology nurses have a valuable role providing knowledge and support to patients transitioning to independent self-care. A better understanding of factors facilitating patients to become experts in their condition may improve longer term outcomes and reduce cost pressures on lymphoedema services. Highlights: Establishing routines for self-management helps normalise life with lymphoedema. Taking ownership of lymphoedema and self-management improves lymphoedema control. Perceived treatment benefit is an enabler for self-management. Women may view differently the same treatment outcome, affecting treatment adherence. Women self-monitor lymphoedema: size, appearance, softness and internal sensations.